Strategies for Improving Teacher Pedagogic Competence Industrial Revolution Era 4.0 - Arif Wicagsono, Muhammad; Muhammad Hamad Al-Nil, Barakat Muhammad Ahmad; Muthoifin (Universitas Muhammadiyah Surakarta, 2023)
This type of research is field research. The subjects of the research were principals and teachers at SMP Muhammadiyah PK Kottabarat Surakarta and SMP Muhammadiyah Al-Kautsar PK. Furthermore, the objects of this research were pedagogical competence and strategies to improve pedagogical competence in the era of Industrial Revolution 4.0, SMP Muhammadiyah PK Kottabarat Surakarta, and SMP Muhammadiyah Al-Kautsar PK. This research employed a case study approach. Thus, data collection was originally from the interview, observation, and documentation. This study concluded that the teachers' pedagogical competence in the era of Industrial Revolution 4.0 at SMP Muhammadiyah PK Kottabarat Surakarta and SMP Muhammadiyah Al-Kautsar PK, had good pedagogical competence, according to pedagogical competency standards of Permendikbud No. 16 of 2007. Teachers understood the character of students through habituation, study assistance, and parent interviews. The teachers understood learning theory and how to develop a curriculum based on al Islam Kemuhammadiyahan curriculum, and sharia curriculum. The teachers created learning tools, models usage, strategies, or selecting learning methods. Teachers employed integrated learning technology and educational platforms like YouTube, zoom, PK Learning, and Edmodo. The teachers provided evaluations in the form of tests, PTS, PAS, and remedial tests. However, they analyzed the assessment results to comprehend the development of students through extracurricular programs, Talent classes, and OSN. The strategy to improve teachers' pedagogical competence was conducted through various educational, training, seminars, supervision, MGMP, scientific studies, and rewarding, training of Tahsin and Tahfidz, Islamic studies through teachers studies, PDM and PCM studies, training graphic design, and IT-based learning applications training.